2022
DOI: 10.3390/plants11182338
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medicago lupulina Interaction with Rhizophagus irregularis in the Determination of Root Metabolome at Early Stages of AM Symbiosis

Abstract: The nature of plant–fungi interaction at early stages of arbuscular mycorrhiza (AM) development is still a puzzling problem. To investigate the processes behind this interaction, we used the Medicago lupulina MlS-1 line that forms high-efficient AM symbiosis with Rhizophagus irregularis. AM fungus actively colonizes the root system of the host plant and contributes to the formation of effective AM as characterized by a high mycorrhizal growth response (MGR) in the host plant. The present study is aimed at dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Recently, various omics approaches have been widely used to study the function of supra-organismal symbiotic PMS, which is formed during the development of arbuscular mycorrhiza [23,26,27,[29][30][31][32]34,35]. These approaches include transcriptomic analysis, which identifies groups of DEGs that are significant for a plant upon interaction with AM fungus [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, various omics approaches have been widely used to study the function of supra-organismal symbiotic PMS, which is formed during the development of arbuscular mycorrhiza [23,26,27,[29][30][31][32]34,35]. These approaches include transcriptomic analysis, which identifies groups of DEGs that are significant for a plant upon interaction with AM fungus [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Special interest is always paid to the improvement of sequencing and transcriptome analyses [19][20][21][22][23]. Studies are underway investigating the influence of AM fungi on the proteome of M. truncatula, Pisum sativum [23][24][25][26][27], and on the metabolome (with gaschromatography-mass spectrometry, GC-MS) of M. truncatula, M. lupulina, P. sativum [26,[28][29][30][31][32], etc. The role of AM transcriptomic studies of M. truncatula, Nicotiana attenuata, P. sativum is remarkable [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Yurkov et al [12] focused on the study of the interaction of the plant and the early stages of the development of arbuscular mycorrhizae (AM), studying the metabolome of the inoculated root of Medicago lupulina in a substrate with low phosphorus. The results obtained indicated that mycorrhization was the determinant of the root metabolite profile rather than the further development of the host plant.…”
Section: Special Issue Contentsmentioning
confidence: 99%
“…Arbuscular mycorrhizae are the associations where a Glomeromycete fungus produces arbuscules, hyphae, and vesicles within root cortex cells [11]. These associations are due to the presence of arbuscules.…”
Section: Introductionmentioning
confidence: 99%